Analisis Pengaruh Adopsi Teknologi Digital dan Literasi Digital Terhadap Kinerja Keuangan UMKM di Indonesia - Annisa, Mutiara; Rusiadi, Rusiadi; Efendi, Bakhtiar (STIE Amkop Makassar, 2025)
This research examines how the adoption of digital technology and digital literacy affects the financial performance of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. With a quantitative approach and using a multiple linear regression model on data from 2013 to 2023, this research finds that digital literacy and the use of e-commerce have a significant positive impact on the profitability of MSMEs. However, the adoption of digital technology and digital payment methods shows a negative, although still significant, impact on the financial performance of MSMEs. These findings indicate that digital transformation can increase the profitability of MSMEs, as long as it is supported by effective implementation strategies, such as training in technology and digital literacy. This research recommends optimizing digitalization programs, providing technological incentives and policy support to maximize the positive benefits of digitalization for the development of MSMEs.